Imitatio Christi and the holy folly of divine violence: the church as ultimate criminal - Meylahn, J. A. (Faculty of Theology, University of the Free State, 2014)
The calling of the church is to follow Christ (imitatio Christi). What does this calling entail? Following Žižek's and Derrida's interpretation of Benjamin's interpretation of law and violence, the paper will argue that the call to follow Christ is not to subvert the law, but as Paul argues - Christ came to destroy the law. In this article, Christ will be interpreted as one who did not counter this violence of the law (state-maintaining violence) with a counter violence of state-forming violence, but completely undermined the justification of both forms of violence (state-forming and state-maintaining) with a divine violence. If the Christ event is read as an exemplary narrative of the post-metaphysics in the linguistic turn in the work of Derrida, this opens up new possibilities for both theology as well as the role of the church within the context of a postmodern world, and these possibilities will be explored.
Keywords: Radical theology; Postmetaphysics; Philosophy of religion; Practical theology